TINGKAT PENGETAHUAN IBU TENTANG PENTINGNYA PERSALINAN DITOLONG TENAGA KESEHATAN DI DUSUN PALELENG DESA KASERALAU KECAMATAN BATULAPPA KABUPATEN PINRANG TAHUN 2018 - Dewi Purnama Windasari (Jurnal Pengabdian Masyarakat Gerakan Aksi Sehat (GESIT), 2018)
Labor is a very complex thing because there is happiness happening before the birth of children but there are risks that may threaten the safety of mother and baby. Maternal Mortality Rate (MMR) in Indonesia is still quite high. Based on Indonesia Demographic and Health Survey (SDKI) in 2015, coverage of labor by health personnel is about 90.88%, which means that there are still 10% labor that is not helped. While data of RISKESDES year 2015 indicate that delivery done at home still high enough that is equal to 29,6%. At Dusun Paleleng Kaseralau Village Batulappa Subdistrict Pinrang District in the year 2017 in August there are 8 childbirths or (34.8%) whose delivery is not helped by health workers from a total of 23 Pairs of Age of Fertile or (100%). Based on the result of activity of knowledge level on prenatal test assisted by health personnel there are 16 people (100%), who know with 7 people (43.8%) while those who do not know 9 people (56.2%), after the extension then the result of knowledge level on post test of labor assisted by health personnel there are 16 people (100%), who know with the number of 16 people (100%).